Exploring the Impact of Education and Awareness on Job Satisfaction among Teacher Trainers - SINGH, SHRIKANT (CV. Rayyan Dwi Bharata, 2026)
The study investigates the function of education and awareness programs in enhancing job satisfaction among teacher trainers in Kanpur, Uttar Pradesh. The objectives of the research were to explore how professional development initiatives and supportive institutional factors contribute to teacher trainers' job satisfaction. An illustration of 106 teacher trainers participated in the research, information gathered by structured questionnaires. The results show that education and awareness programs, including stress management and professional growth opportunities, significantly enhance job satisfaction by improving self-efficacy and reducing job-related stress. Furthermore, institutional support such as recognition, manageable workloads, and a collaborative work setting was discovered to have a strong positive impact on job satisfaction, confirming the theory that these elements are key drivers in improving the satisfaction and keeping of teacher trainers. Statistical analysis revealed that there is a substantial relationship between job satisfaction and recognition (r = 0.81), in addition to between education programs and contentment at work (r = 0.72). The study comes to the conclusion that investing in continuous professional development and establishing a helpful workplace are crucial. Strategies for enhancing teacher trainers' contentment at work and overall performance. Educational institutions should prioritize these factors to improve trainer retention and promote a positive organizational culture. The findings underscore the requirement for laws that uphold the personal and professional well-being of teacher trainers to foster a motivated and effective workforce.